The Effect of Glutamine and Glucose Supplementation on Maximal Aerobic Power and Hemoglobin Concentration in Athlete Young Girls - Banafsheh Amin; Mohammad Karimi (The Society of Aging and Physical Activity (SAPA), 2017)
Background. Maximal Aerobic Power is related to many quantities and qualities such as supplements. Objectives. The purpose of the present study was to describe the effect of short-term supplementation of glutamine and glucose on hemoglobin and maximum aerobic power in female athletes. Methods. In this quasi-experimental study, 40 female athletes (age 21.9±2.6 years, height 161.8±5.1 cm, weight 57.8±6.3 kg, BMI 21.9±1.5 kg/m2) volunteered to participate in the present study. Before intervention, the participants were divided randomly into four equal groups (each group=10); placebo, glutamine supplement (0.3 g/kg body weight), glucose supplement (1.0 g/kg body weight) and glutamine-glucose combination supplement. VO2max measured using Bruce protocol and also, hemoglobin concentrations were measured via blood sampling at 12h fasting state. The experimental groups did two-week supplementation accompanied with moderate intensity aerobic exercise, three sessions per week and (45-60) minutes per session. At the end of period of supplementation VO2max and hemoglobin values were measured again. Results. Short-term supplementation of glutamine (P=0.0001), glucose (P=0.0001) and glutamine-glucose (P=0.0001) improved significantly VO2max values. Also, hemoglobin levels increased significantly in glutamine (P=0.012) and glutamine-glucose (P=0.0001) groups. Conclusion. It seems that short-term supplementation of glutamine, glucose and glutamine-glucose may lead to improvement in aerobic performance in young female athletes.